Analysis of Teacher’s Role in Freedom Writers Film - Dewa, Dewa Ayu Ratih; Wedayanthi, Luh Made Dwi; Suardana, I Putu Oka (The Future of Education Journal, 2025)
This research is motivated by the importance of the teacher's role in creating a meaningful learning process, as depicted in the film "Freedom Writers." The purpose of this study is to analyze the role of the teacher shown in the film based on Jeremy Harmer's theory of the teacher's role and to examine the emerging discourse using Teun A. van Dijk's Critical Discourse Analysis (CDA) model. This study employed a descriptive qualitative method, with data collection techniques through observation and documentation of dialogue and scenes in the film. The results indicate that the teacher in "Freedom Writers" plays the role of controller, prompter, participant, resource, and tutor. Critical discourse analysis reveals that text structure, social cognition, and social context significantly influence the portrayal of the teacher's role in the film. This research is expected to inspire and serve as a reflection for teachers and prospective teachers in educating students.